Language Without Words: light and contrast in audio description - Maszerowska, Anna (The Journal of Specialised Translation, 2013)
The importance of the inclusion of directorial vision and cinematographic language cues in film audio description scripts is a claim that has long been maintained in the literature related to media accessibility. This article aims to analyse the existing audio descriptions of light and contrast patterns. The first part presents an overview of the functions attributed to luminance in the field of Film Studies. The author then investigates the state of the art in the related literature on media accessibility and audio description. Guidelines and research papers are consulted in order to establish the stance on the issue from both a practical and scholarly point of view. The second part presents an analysis of a corpus of six professionally audio described films and discusses the strategies employed by the describers when confronted with certain lighting set-ups. Finally, the article concludes with a set of recommendations for future research in the area.